CLCA2 as a Novel Immunohistochemical Marker for Differential Diagnosis of Squamous Cell Carcinoma from Adenocarcinoma of the Lung. (7th December 2014) - Shinmura, Kazuya; Igarashi, Hisaki; Kato, Hisami; Kawanishi, Yuichi; Inoue, Yusuke; Nakamura, Satoki; Ogawa, Hiroshi; Yamashita, Takashi; Kawase, Akikazu; Funai, Kazuhito; Sugimura, Haruhiko
Abstract : Recent progress in targeted therapy for lung cancer has revealed that accurate differential diagnosis between squamous cell carcinoma (SCC) and adenocarcinoma (ADC) of the lung is essential. To identify a novel immunohistochemical marker useful for differential diagnosis between the two subtypes of lung cancer, we first selected 24 SCC-specific genes and 6 ADC-specific genes using data (case number, 980) from the Cancer Genome Atlas (TCGA) database. Among the genes, we chose the CLCA2 gene, which is involved in chloride conductance and whose protein expression in lung cancer is yet to be characterized, and evaluated its protein expression status in 396 cases of primary lung cancer at Hamamatsu University Hospital. Immunohistochemical analysis revealed a significantly higher CLCA2 expression level in the SCCs than in the ADCs ( P < 0.0001 ) and also a significantly higher frequency of CLCA2 protein expression in the SCCs (104/161, 64.6%) as compared with that in the ADCs (2/235, 0.9%) ( P < 0.0001 ; sensitivity 64.6%, specificity 99.1%). The CLCA2 protein expression status was associated with the histological tumor grade in the SCCs. These results suggest that CLCA2 might be a novel excellent immunohistochemical marker for differentiating between primary SCC and primary ADC of the lung.